A Comprehensive Review on Grid-forming Inverter: Potential and Future Trends - SAMUEL YUSUF; ADAMU ABUBAKAR (Majlesi Journal of Electrical Engineering)
There is growing commitment to phase-out the conventional fossil-fuel based power stations to decentralized power generation with high share of renewable energy sources that is based on low-emission to meet the various techno-economic, environmental and secure energy requirements. This paradigm shift from conventional generators to the inverter-dominated DGs/RESs, has come with some technical challenges of low inertia, frequency instability, harmonic distortion etc. The challenges require effective and efficient inverter-based power system control for a reliable and stable grid interface. Based on the way inverters functions, it is grouped into three categories: grid-feeding, grid-supporting, and grid-forming. Several control schemes have been proposed for grid-forming inverter; these control schemes are based on the concept of Virtual synchronous machine, Power synchronization control, and Direct power control. This paper presents a comprehensive review on the recent advancements in grid-forming inverter control technologies. This review covers different control techniques that have been successfully implemented for the inverter-based power system to grid interface, benefits and challenges of attaining the estimated 100% non-synchronous power generation. The cornerstone of the survey is to also establish state-of-the-art on the grid-forming inverter and identify future research areas for improving the existing techniques and developing novel ones.